Adaptation and Psychometric Properties of The Indonesian Version of The Financial Well-Being Scale - Ariffani Rachmansyah Nur; Theda Renanita (Universitas Muhammadiyah Surakarta, 2025)
Financial well-being is a key indicator of individual welfare and family financial resilience. However, the absence of a standardized Indonesian measurement tool hinders research in this area. This study aimed to adapt the widely used unidimensional In Charge Financial Distress/Financial Well-Being (IFDFW) scale and to provide comprehensive validity evidence for its use in Indonesia. The research was conducted in two main stages: a cross-cultural adaptation and a psychometric validation. Data were collected from 150 workers aged 20–50 across Indonesia using an online survey and a purposive sampling technique. The analysis included Aiken's V and FVI coefficients to assess content validity and response processes, as well as Confirmatory Factor Analysis (CFA) to confirm the scale's internal structure. The study also examined the scale's convergent validity through correlation tests with the Personal Financial Wellness Questionnaire. The results showed that the adapted scale has acceptable content validity (Aiken's V = 0.68) and a high level of clarity (FVI = 0.88). The CFA demonstrated good model fit (CFI = 0.97, TLI = 0.96, RMSEA = 0.08) and high internal reliability (w = 0.89). Additionally, the scale showed significant correlations with the subjective perspective, financial behaviour, and financial satisfaction dimensions of financial wellness. These findings confirm that the 8-item Indonesian version of the IFDFW scale is a valid and reliable instrument. Researchers can use this tool to advance financial well-being studies and for practitioners to design effective financial literacy interventions in Indonesia